A multilevel analysis of mortality following acute myocardial infarction in Norway: do municipal health services make a difference?. Issue 11 (5th November 2015) - Ambugo, Eliva Atieno; Hagen, Terje P
Abstract : Objectives: Studies link area features such as neighbourhood socioeconomic deprivation to poor health outcomes. However, there is a paucity of research based on representative data investigating the effects of area-level health services on mortality. This study examines the extent to which municipal health services account for municipal variation in all-cause and cardiovascular disease (CVD) mortality. We hypothesise that unfavourable municipal features (eg, fewer available places for rehabilitation) are associated with higher risk of mortality after accounting for patients' characteristics. Design: Population data from Norwegian national/municipal registrars are analysed using multilevel logistic regression in this prospective cohort study. Setting and participants: The analytic sample (9412 patients aged 18+ from 336 municipalities) constitutes 87.7% of the nationwide population of Norwegian adults who were hospitalised for acute myocardial infarction (AMI) in 2009 and discharged alive. Primary outcome measures: All-cause and CVD mortality occurring within 365 days after the first day of hospitalisation for AMI. Results: There was a small but significant variation at the municipal level in all-cause mortality (0.5%; intraclass correlation coefficient=0.005) but not CVD mortality. There were no significant fixed effects of municipal health services on mortality in bivariate models. Patients' characteristics (eg, gender, comorbidities) fully accounted for the observed municipal variation in mortality. Being male versus female (OR=1.21, 95% CI 1.02 to 1.43), or having been previously diagnosed with dementia versus not (OR=2.06, 95% CI 1.53 to 2.77) were also linked to higher odds of death. Conclusions: Municipal variation in all-cause mortality for Norwegian patients with AMI appears to be driven not by differences across municipalities in health service levels, but by differences across municipalities in the composition of patients. Focusing on chronic disease prevention and treatment, and tackling personal and structural risk factors embedded within patients' sociodemographic characteristics, may be especially beneficial for longevity.